Analisis dimensi iklim keselamatan terhadap keselamatan pasien di rumah sakit - Liana, Duta; Dwijayanti, Fifi; Fauziah, Nuraini (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Patient safety is a crucial aspect of healthcare systems, reflecting the quality and effectiveness of services. Despite technological advancements, patient safety incidents continue to be a significant global challenge. A total of 5,710 patient safety incidents were recorded in Indonesia in 2023.Objectives: This study aims to analyze the dominant factors that are significantly related to patient safety and provide evidence-based strategies for healthcare facilities to improve safety protocols. Methods: A cross-sectional study design was employed using secondary data from the Hospital Accreditation Committee (KARS). A sample of 178 hospitals was purposively selected in the Greater Jakarta area, operating continuously, and registered in the KARS database for the period 2018–2020. Independent variables included hospital characteristics and safety climate dimensions. Bivariate analysis used chi-square, and multivariate analysis used multiple logistic regression.Results: Multivariate analysis shows that the dominant factors associated with patient safety are reporting and organizational learning. Hospitals with poor reporting had 3,3 times higher odds of experiencing poor/adverse patient safety outcomes. Hospitals with poor organizational learning had 2,3 times higher odds of experiencing poor/adverse patient safety outcomes.Conclusion: Strengthening reporting mechanisms and fostering an organizational learning climate are important strategies for improving patient safety. Hospitals need to prioritize these factors while continuing to pay attention to teamwork and communication through the development of non-punitive reporting systems, training staff in reflective learning, and integrating reporting into KARS to create a safer healthcare environment.